EFFECTIVENESS OF TRADITIONAL ENGKLEK GAMES TO IMPROVE SOCIAL SKILLS OF GROUP B CHILDREN AT TK AL-FATH PRESCHOOL BANDA ACEH - Cut Fazlil Hanum; Rini Rovika (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The background in this study is that children have low social skills such as not wanting to cooperate with groups, and not wanting to socialize with other children. Therefore the problem formulation of this study .